Initial Reports of the Deep Sea Drilling Project 1975
DOI: 10.2973/dsdp.proc.28.129.1975
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic Rocks of Naturaliste Plateau, Eastern Indian Ocean, Site 264, DSDP Leg 28

Abstract: The upper part of a pile of andesitic volcanogenic sediments underlying Upper Cretaceous chalk was sampled on the Naturaliste Plateau at DSDP Site 264. Material recovered from the pile is entirely volcanic and is composed mainly of rock fragments that probably represent coarse clasts in the sequence. Minor conglomerate in which pebbles of volcanic rock are embedded in a highly altered tuffaceous matrix was recovered at two levels. In general, high alteration makes interpretation of original compositions uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Although our samples are altered, they are not nearly as altered as the set of igneous rocks from DSDP Site 264, to the south (Fig. 1), examined and analysed in part by Ford (1975a). As well, analyses of igneous rocks from oceanic plateaus such as the Naturaliste are relatively rare, and so those presented here may have intrinsic value.…”
Section: The Basaltsmentioning
confidence: 88%
See 3 more Smart Citations
“…Although our samples are altered, they are not nearly as altered as the set of igneous rocks from DSDP Site 264, to the south (Fig. 1), examined and analysed in part by Ford (1975a). As well, analyses of igneous rocks from oceanic plateaus such as the Naturaliste are relatively rare, and so those presented here may have intrinsic value.…”
Section: The Basaltsmentioning
confidence: 88%
“…' Jongsma & Petkovic (1977) paraphrased this opinion, as did other authors who had dealt with the plateau and adjacent regions, e.g. Markl (1974Markl ( , 1978, and Ford (1975a). Our objective was to report on the dredged continental material, but our examination soon showed that no undoubted continental rocks were present; the rock component was made up of basaltic lava cobbles.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Due to the sparse data available, the origins of the Naturaliste Plateau are not fully understood. Geophysical seismic and potential field studies (Petkovic, 1975;Jongsma and Petkovic, 1977;Borissova, 2002;Direen et al, 2007) and chemical analysis of dredged material (Halpin et al, 2008) and borehole cores (Ford, 1975) suggest Figure 1. Study area offshore Cape Leeuwin, Australia.…”
Section: Location and Geological Setting Of The Study Areamentioning
confidence: 99%